2021
DOI: 10.3390/ani11102964
|View full text |Cite
|
Sign up to set email alerts
|

Pet Reptiles—Are We Meeting Their Needs?

Abstract: The ability to meet the needs of each species in captivity is at the heart of the ethical debate on the acceptability of keeping reptiles and other animals as pets. Little is known about the ability of reptile owners to understand their pets’ behavior and to meet their welfare requirements. In this study, we surveyed pet reptile owners in Portugal (N = 220) to assess their behavioral knowledge and the provision of essential husbandry needs. Although two-thirds of respondents (68%) scored very good to excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Motivations were overall complex and multidimensional, with keepers having more than a single reason for keeping reptiles as pets. This finding is in agreement with other studies that have also shown affection and emotional relations as well as a variety of other motivations for keeping exotic pets [ 20 , 29 , 30 ]. For example, in Portugal, most keepers described affection toward reptiles to explain the acquisition and keeping of reptiles as pets, while convenience, entertainment, companionship, and duty of care were the motivations for long-term keeping [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Motivations were overall complex and multidimensional, with keepers having more than a single reason for keeping reptiles as pets. This finding is in agreement with other studies that have also shown affection and emotional relations as well as a variety of other motivations for keeping exotic pets [ 20 , 29 , 30 ]. For example, in Portugal, most keepers described affection toward reptiles to explain the acquisition and keeping of reptiles as pets, while convenience, entertainment, companionship, and duty of care were the motivations for long-term keeping [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with other studies that have also shown affection and emotional relations as well as a variety of other motivations for keeping exotic pets [ 20 , 29 , 30 ]. For example, in Portugal, most keepers described affection toward reptiles to explain the acquisition and keeping of reptiles as pets, while convenience, entertainment, companionship, and duty of care were the motivations for long-term keeping [ 20 ]. In Greater Jakarta, Indonesia, the motivations for keeping snakes were mainly influenced by seeing close peers keeping snakes, visiting snake exhibitions, social media, or gifts [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…13 Amphibians and reptiles are kept as pets by about 4% of Australian households, 14 but there is very little research investigating their welfare. Data regarding the welfare of pet snakes 3 and lizards 2 in Australia have been previously reported, and turtles have been studied in a sample of Portuguese owners, 15 but not in Australia. Turtles are the most common pet reptile species in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Providing pet owners with accurate information about pet care is essential for the welfare of their animals, especially as many owners will actively seek advice on what care to provide. 1,2 Accurate information is even more valuable when there are welfare concerns about the housing and husbandry of animals, as is the case with many less popular companion species, [3][4][5][6] including rats. 7 However, developing good care guidelines for pet rats poses a number of challenges.…”
Section: Introductionmentioning
confidence: 99%